Reinforcement Interval and Interresponse Time Reinforcement as Determinants of Response Rate - Kuch, Oscar Dennis (My University, 1975)
Reinforcement may affect responding by strengthening a response so as to increase its frequency of occurrence and by differentiating a response with respect to some of its properties. It has been suggested that response rate is controlled by the strengthening effect of reinforcement on responding and by the differential reinforcement of the time between responses, the interresponse time. The strengthening and differentiating effects of reinforcement on response rate are usually confounded in studies of responding on simple reinforcement schedules. This thesis analyzed the effects of reinforcement interval (a strengthening variable) and interresponse time reinforcement (a differentiating variable) on response rate by independently manipulating them over a range of values. Food-deprived pigeons pecking illuminated disks for food reinforcement were exposed to novel reinforcement schedules which allowed simultaneous differential reinforcement of interresponse times and control of reinforcement interval. With these schedules interresponse time reinforcement was the principal determinant of response rate while reinforcement interval played a secondary role. Although both variables made independent contributions to the determination of response rate, they did not interact over the range of values investigated. This thesis documents the existence of separable strengthening and differentiating effects of reinforcement on response rate and emphasizes the importance of interresponse time differentiation in the determination of response rate.
Keywords: Psychology; Psychology